2019
DOI: 10.1103/physreva.100.052511
|View full text |Cite
|
Sign up to set email alerts
|

Precision measurements of the gradient of the Casimir force between ultraclean metallic surfaces at larger separations

Abstract: We report precision measurements of the Casimir interaction at larger separation distances between the Au-coated surfaces of a sphere and a plate in ultrahigh vacuum using a much softer cantilever of the dynamic atomic force microscope-based setup and two-step cleaning procedure of the vacuum chamber and test body surfaces by means of UV light and Ar-ion bombardment.Compared to the previously performed experiment, two more measurement sets for the gradient of the Casimir force are provided which confirmed and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
109
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(118 citation statements)
references
References 83 publications
(163 reference statements)
9
109
0
Order By: Relevance
“…The measurement data of numerous precise experiments excluded this prediction and were found in good agreement with the Lifshitz theory if the electromagnetic response of a metal is described using the optical data of a metal extrapolated by the dissipationless plasma permittivity (see a review of the first experiments by R.S. Decca in [13]) and later experiments [14][15][16][17][18][19][20][21]). The situation in the field was also reviewed in [22].…”
Section: Introductionmentioning
confidence: 75%
“…The measurement data of numerous precise experiments excluded this prediction and were found in good agreement with the Lifshitz theory if the electromagnetic response of a metal is described using the optical data of a metal extrapolated by the dissipationless plasma permittivity (see a review of the first experiments by R.S. Decca in [13]) and later experiments [14][15][16][17][18][19][20][21]). The situation in the field was also reviewed in [22].…”
Section: Introductionmentioning
confidence: 75%
“…Based on this result, the authors of [12] concluded that the Nernst theorem is not fulfilled by the Drude model, claiming its thermodynamic inconsistency. The distrust in the Drude description can be understood within a broader context involving room temperature experimental results for the Casimir force between a gold coated sphere and a plane: The measurements performed in a range of distances 1 µm [86][87][88][89][90] are in disagreement with the prediction obtained using the Lifshitz formula [91] and the Drude model. They agree, however, with a theoretical description where no further changes are made beside setting the dissipation rate to zero, the so-called plasma model.…”
Section: Nernst Theorem and The Plasma-drude Controversymentioning
confidence: 93%
“…This article discusses the situation when a person, being at some distance from the center of the diameter of the oil spill, during his sudden outbreak, for some time (about 3-5 s) remains in shock (determined by the reaction time to the outbreak, turn, start of running), then begins to run away in the direction of decreasing the heat flux intensity to a safe distance determined by the intensity of the acting heat flux of 1.4 kW/m2 [21][22][23][24][25]. However, during the movement of a person to the border of the safe zone, the effect of thermal radiation continues on him.…”
Section: Dose Of Thermal Radiation J/m2mentioning
confidence: 99%